Psycholinguistic implications for successful communication: The case of face-to-face dyadic interaction - Kamisznikow, Agnieszka (Scripta Neophilologica Posnaniensia, 2018)
Psycholinguistic implications for successful communication: The case of face-to-face dyadic interaction